The same but different: A social semiotic analysis of website interactivity as discourse. Issue 2 (April 2022) - Vigild Poulsen, Søren
The aim of this article is to explore website interactivity as discourse. Whereas the use of writing, images and layout in web design has been explored extensively, interactivity, that is, interactions between a web user and the website system, remains an underdeveloped area of discourse studies. To analyze interactivity as discourse, the article uses data from a research project on offline and online shopping for electronics, viewing the offline-online relationship as recontextualization in the sense that webshop interactivity (together with other design elements) represents and transforms in-store shopping actions. Using a methodology that combines analytical framework for interactive sites and approach to discourse analysis, the article maps cursor resources and interactive webshop features as actions and compares them to the actions that constitute in-store shopping. On this basis, the article offers reflections on how interactivity plays a defining role in the digital resemiotization of social practices.